2018
DOI: 10.1016/j.econmod.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Stock market development and economic growth: Empirical evidence from China

Abstract: It is important to understand the interplay between stock market and real economy to figure out the various channels through which financial markets drive economic growth. In the current study we investigate this relationship for Chinese economy, the fastest growing and largest emerging economy in the world. Using the methodology of unit root testing in the presence of structural breaks and using an ARDL model, we find that Global Financial Crises had a significant impact on both China's real sector and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 48 publications
5
115
0
7
Order By: Relevance
“…Using the data of 20 countries, Madsen, Dzhumashev, and Yao (2013) find that the relation of stock return and economic growth is positive over and no relation existed outside the period. Pan and Mishra (2018) find that the relationship between stock market and real sector of the economy is negative but miniscule in China.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the data of 20 countries, Madsen, Dzhumashev, and Yao (2013) find that the relation of stock return and economic growth is positive over and no relation existed outside the period. Pan and Mishra (2018) find that the relationship between stock market and real sector of the economy is negative but miniscule in China.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The relatively short history of China's stock market that was founded at the end of 1991 determines the sampling period of data as 1992q1-2017q4. We is usually considered to be more closely related to China's economic growth than other indices and is widely used by many empirical studies (e.g., Giannellis & Papadopoulos, 2016;Hu, 2010;Pan & Mishra, 2018). The data of quarterly closing prices of the S.H.A.S.H.R.…”
Section: Datamentioning
confidence: 99%
“…Obvious choices would be to use Spearman rank order correlations (Ji et al, 2013;van der Burg & de Leeuw, 1983) or to use average mutual information (Chen et al, 2008;Prichard et al, 1996;Wing et al, 2016) instead of Pearson linear correlation. In analogy with some stock market indices (Arnott et al, 2005;Pan & Mishra, 2018), equal weighting should be assessed. And since an "activity" index is sought, weights chosen by the time derivatives of variables should also be explored.…”
Section: Advancing the Development Of Composite Indices For The Magnementioning
confidence: 99%
“…This composite magnetospheric index E (1) has a strong analogy with a "stock market index" that is created from multiple individual stocks whose values are summed to construct the single stock market index (Comer, 1929;Lo, 2016). In creating the stock index, weighting coefficients based on stock price, on the number of outstanding shares, on the trading volume, on revenues, or on corporate value are used in the summing of the multiple stock values (Arnott et al, 2005;Pan & Mishra, 2018). The time-dependent stock market index is a better indicator of economic behavior than is the time-dependent value of any single stock (Fama, 1981;Prodhan et al, 2015;Schwert, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The results from this study are realistic because, when the stock market performs well, the impact is transferred to businesses and this in turn impacts on the overall economic growth. Pan and Mishra (2016), investigated stock market development and economic growth in China (the largest and fastest growing economy in the world) using the ARDL method and discovered that the global financial crises had a significant impact on both China's real sector and financial sector. The results also showed that the share market has a long run negative association with the real sector of the economy.…”
Section: IImentioning
confidence: 99%